2008
DOI: 10.1016/j.jcrs.2008.04.040
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin glue–assisted sutureless posterior chamber intraocular lens implantation in eyes with deficient posterior capsules

Abstract: We report a new surgical technique that uses biological glue to implant a posterior chamber intraocular lens (PC IOL) in eyes with a deficient or absent posterior capsule. Two partial-thickness limbal-based scleral flaps are made 180 degrees apart diagonally, and the haptics of the PC IOL are externalized to place them beneath the flaps. Fibrin glue is used to attach the haptics to the scleral bed, beneath the flap. This simple method of PC IOL implantation requires no specially designed haptics. It provides g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
290
0
10

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 462 publications
(312 citation statements)
references
References 27 publications
3
290
0
10
Order By: Relevance
“…In this retrospective case series, 53 eyes of 53 patients who underwent fibrin glue-assisted posterior chamber IOL implantation 9 were analysed after 1 year. All eyes operated using this procedure from December 2007 to May 2008 were included and followed up for 12 months.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this retrospective case series, 53 eyes of 53 patients who underwent fibrin glue-assisted posterior chamber IOL implantation 9 were analysed after 1 year. All eyes operated using this procedure from December 2007 to May 2008 were included and followed up for 12 months.…”
Section: Methodsmentioning
confidence: 99%
“…[2][3][4][5][6][7][8] Fibrin glue-assisted posterior chamber (PC) IOL implantation is a new technique started in December 2007 in eyes with deficient capsular support. [9][10][11][12] The purpose of this article is to evaluate the post-operative outcome, namely, visual prognosis and complication profile, of eyes operated using this technique at the end of 1 year.…”
Section: Introductionmentioning
confidence: 99%
“…Fibrin glue has also been used to assist in posterior chamber intraocular lens implantation in eyes with capsular support deficiency with good visual acuity outcome and no postoperative complications [130,131]. Buschman et al also reported success in using fibrin glue for closing anterior lens capsule wounds [132].…”
Section: Lens Surgerymentioning
confidence: 99%
“…5 In-the-bag IOL dislocation, however, usually occurs several years after cataract surgery and is thus thought to depend on slowly progressive dehiscence of the zonules. 6,7 When endocapsular IOL placement is not possible, the choices include sutured scleral-fixated IOLs, 8,9 sutureless scleral-fixated IOLs, 10,11 iris-fixated IOLs, 12 iris-claw IOLs, 13 or anterior chamber (AC) IOLs. 14 However, scleral-fixated IOLs are subject to problems such as suture degradation, pseudophacodonesis, endophthalmitis, and late IOL decentration owing to suture-related complications.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] Iris-fixated or iris-claw IOLs have fewer posterior segment complications, but they can lead to chronic pigment release from the iris, which can cause inflammation and spontaneous iris disencalvation. 18 Many surgical procedures have been introduced to reduce these complications; for example, Agarwal et al 11 reported an effective sutureless IOL scleral fixation as a new surgical technique that uses biological glue to implant a PC IOL in eyes with a deficient or absent posterior capsule. This technique of PC IOL implantation is appropriate for eyes without posterior capsules and is performed easily with the available IOL designs.…”
Section: Introductionmentioning
confidence: 99%